Perovskite quantum dot / PVDF light-emitting film and preparation method and application thereof

By performing alkaline immersion treatment in perovskite quantum dot/PVDF composite film, the shortcomings in luminous efficiency and stability of perovskite quantum dot/PVDF luminescence film are solved, and efficient and stable luminescence performance is achieved. It is suitable for a variety of optoelectronic devices and display technology applications.

CN119899657AActive Publication Date: 2025-04-29MINDU INNOVATION LAB

Patent Information

Application Number
CN202510061778.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-29
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The existing perovskite quantum dot/PVDF luminescent films have shortcomings in terms of luminescence efficiency and stability, especially in the red light region.

Method used

By soaking the perovskite quantum dot/PVDF composite membrane in an alkaline solution, the PVDF deHF reaction is used to form a conjugated double bond structure, and the perovskite quantum dot surface defect is passivated by F ions in situ.

Benefits of technology

It significantly improves the luminous efficiency and long-term stability of the film, is suitable for high humidity and high temperature environments, and is suitable for optoelectronic devices, display technology and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899657A_ABST
    Figure CN119899657A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite quantum dot / PVDF luminescent film and a preparation method and application thereof, and relates to the field of optoelectronic materials. The preparation method of the perovskite quantum dot / PVDF light-emitting thin film comprises the step of carrying out soaking treatment on a perovskite quantum dot / PVDF composite film, wherein the soaking treatment is that the perovskite quantum dot / PVDF composite film is soaked in an alkaline solution with the pH value larger than 7. According to the preparation method, PVDF is subjected to HF removal reaction through soaking treatment of an alkali solution, a conjugated double-bond structure is formed, surface defects of perovskite quantum dots are passivated in situ by using F ions, and the luminous efficiency and long-term stability of the thin film are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optoelectronic materials, in particular to a perovskite quantum dot / PVDF luminescent film and a preparation method and application thereof. Background Art

[0002] As an emerging semiconductor nanomaterial, perovskite quantum dots have attracted widespread attention in the field of optoelectronic devices due to their unique optical properties, such as high fluorescence quantum yield, narrow emission bandwidth and tunable emission wavelength. In particular, in recent years, perovskite quantum dots have made important progress in the application of LEDs, photovoltaic devices, lasers, etc. However, despite their excellent optical properties, perovskite quantum dots still face some key challenges, especially in terms of luminescence efficiency and stability. There are a large number of defect states on the surface of perovskite quantum dots, which can lead to non-radiative recombination and significantly reduce the luminescence efficiency. In particular, for red-light perovskite quantum dots (such as CH3NH3PbI3, FAPbI3), their surface defects are more serious, resulting in low luminescence efficiency. In addition, surface defects can also accelerate the aging and decomposition of quantum dots, affecting their long-term stability, especially in harsh environments such as high temperature and high humidity, where this aging phenomenon is more obvious.

[0003] Polyvinylidene Fluoride (PVDF) is a high-performance polymer with good mechanical properties, chemical stability and electrical properties. It is widely used in battery separators, sensors, coating materials and other fields. However, the inherent non-polar properties of PVDF limit its application in luminescent materials. Specifically, the interface compatibility between perovskite quantum dots and PVDF is poor, resulting in uneven dispersion of quantum dots in the PVDF matrix, affecting the luminescence efficiency.

[0004] In summary, the existing perovskite quantum dot / PVDF luminescent film has many deficiencies in terms of luminescence efficiency and stability, especially in the red light region. Therefore, the development of a perovskite quantum dot / PVDF luminescent film and its preparation method that can significantly improve the luminescence efficiency and stability has important research significance and application value. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing a perovskite quantum dot / PVDF luminescent film. The preparation method significantly improves the luminous efficiency and stability of the perovskite quantum dot / PVDF luminescent film through alkali treatment, and realizes efficient modification of the perovskite quantum dot / PVDF composite film to meet the demand for high-performance luminescent materials in the fields of optoelectronic devices, display devices, etc.

[0006] The present invention also provides a perovskite quantum dot / PVDF luminescent film prepared by the above preparation method.

[0007] The present invention also provides application of the perovskite quantum dot / PVDF luminescent film.

[0008] The present invention adopts the following technical solutions:

[0009] A method for preparing a perovskite quantum dot / PVDF luminescent film, the preparation method comprising soaking the perovskite quantum dot / PVDF composite film in a solution having a pH value greater than 7. The solution having a pH value greater than 7 is an alkaline solution, which may be a weak alkaline solution or a strong alkaline solution, preferably a strong alkaline solution.

[0010] Among them, the OH of the solution - The molar concentration ranges from 0.1 M (mol / L) to 20 M.

[0011] Wherein, the treatment time of the immersion treatment is 1 minute to 10 hours.

[0012] Wherein, the soaking treatment time is 30 minutes to 5 hours.

[0013] Wherein, the immersion treatment temperature is 20°C to 100°C; or, the immersion treatment is carried out under stirring or ultrasonic conditions.

[0014] The preparation method further comprises the steps of cleaning and drying the composite membrane after the immersion treatment.

[0015] Wherein, after cleaning and drying, the preparation method further comprises the step of annealing the composite membrane, the annealing temperature is 20° C. to 150° C., and the annealing time is 10 minutes to 2 hours.

[0016] Furthermore, the solution is a hydroxide solution, a carbonate solution or a bicarbonate solution.

[0017] Correspondingly, the present invention also provides the perovskite quantum dot / PVDF luminescent film prepared as above.

[0018] The application of the above-mentioned perovskite quantum dot / PVDF luminescent film, the perovskite quantum dot / PVDF luminescent film is applied to Micro-LED, quantum dot light-emitting diode display, solar cell or photodetector.

[0019] The beneficial effects of the present invention are as follows:

[0020] (1) The present invention uses alkaline solution immersion treatment to cause PVDF to undergo HF removal reaction to form a conjugated double bond structure, and uses F ions to in-situ passivate the surface defects of perovskite quantum dots, thereby significantly improving the luminescence efficiency and long-term stability of the film.

[0021] (2) This method is simple, easy to operate, low-cost, and suitable for mass production. The prepared film exhibits excellent performance under high humidity and high temperature environments. It is suitable for optoelectronic devices, display technology, biosensors and other fields, and has significant innovation and practical value. It is especially suitable for the manufacture of various advanced electronic and optoelectronic devices such as Micro-LED, liquid crystal display backlight, quantum dot light-emitting diode (QLED) displays, solar cells, photodetectors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The figure is a comparison chart of the luminescence spectra of the thin films obtained in Example 1 of the present invention and Comparative Example 1.

[0023] Figure 2 The figure is a comparison chart of the luminescence spectra of the thin films obtained in Example 2 of the present invention and Comparative Example 2.

[0024] Figure 3 This is a comparison chart of the luminescence spectra of the thin films obtained in Example 3 of the present invention and Comparative Example 3.

[0025] Figure 4 This is a comparison chart of the luminescence spectra of the thin films obtained in Example 4 of the present invention and Comparative Example 4.

[0026] Figure 5 This is a comparison chart of the luminescence spectra of the thin films obtained in Example 5 of the present invention and Comparative Example 5. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0028] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0029] A method for preparing a perovskite quantum dot / PVDF luminescent film, the preparation method comprising soaking the perovskite quantum dot / PVDF composite film in a solution, wherein the pH value of the solution is greater than 7. A solution with a pH value greater than 7 is an alkaline solution, which may be a strongly alkaline solution or a weakly alkaline solution. The solution is a hydroxide solution, a carbonate solution or a bicarbonate solution. In the present invention, the OH in the solution is preferably - The molar concentration of OH is 0.1 M to 20 M. More preferably, the solution contains - The molar concentration is 1M to 5M.

[0030] The inventors found that alkaline treatment causes PVDF to undergo a HF removal reaction to form a conjugated double bond structure, and that F ions can in situ passivate surface defects of perovskite quantum dots, significantly improving the luminescence efficiency and stability of the film.

[0031] Wherein, the treatment time of the immersion treatment is 1 minute to 10 hours; the temperature of the alkali treatment is 20°C to 100°C.

[0032] Preferably, the soaking treatment is carried out under stirring or ultrasonic conditions to ensure the uniformity of the treatment.

[0033] Among them, perovskite quantum dots include but are not limited to lead halide perovskite materials such as CsPbX3 (X = Cl, Br, I), CH3NH3PbX3 (X = Cl, Br, I), and other types of perovskite materials such as methylamine lead iodine (MAPbI3), formamidine lead iodine (FAPbI3), etc.

[0034] Wherein, the molecular weight range of the PVDF is 10000 to 1000000 Da, preferably 50000 to 800000 Da.

[0035] In one embodiment, the preparation method comprises the following steps:

[0036] (1) Soaking treatment: the perovskite quantum dot / PVDF composite membrane is soaked in a solution with a pH value greater than 7;

[0037] (2) Cleaning and drying: The composite membrane that has been soaked is cleaned and dried. Deionized water is used for cleaning, the drying temperature is 40°C to 80°C, preferably 60°C, and the drying time is 1 hour to 24 hours, preferably 2 hours to 6 hours.

[0038] In another embodiment, the preparation method comprises the following steps:

[0039] (1) Soaking treatment: the perovskite quantum dot / PVDF composite membrane is soaked in a solution with a pH value greater than 7;

[0040] (2) Cleaning and drying: The composite membrane that has been soaked is cleaned and dried. Deionized water is used for cleaning, the drying temperature is 40°C to 80°C, preferably 60°C, and the drying time is 1 hour to 24 hours, preferably 2 hours to 6 hours.

[0041] (3) Annealing: The cleaned and dried composite film is annealed at a temperature of 20°C to 150°C for a time of 10 minutes to 2 hours to further improve the crystallinity and optoelectronic properties of the film.

[0042] Among them, perovskite quantum dots can be synthesized by in-situ growth method, hot injection method and room temperature crystallization method, and the perovskite quantum dots can be evenly dispersed in the PVDF matrix by spin coating, spray coating, scraping coating and other processes.

[0043] Preferably, the perovskite quantum dot / PVDF composite film can be prepared by the following method:

[0044] 1. Preparation of perovskite precursor solution

[0045] 1.1 PVDF solution preparation

[0046] PVDF powders with different molecular weights (Mw = 10,000 to 1,000,000 Da, preferably 50,000 to 800,000 Da) were selected and dissolved in mixed solvents consisting of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in different volume ratios (DMF:DMSO = 1:0, 5:1, 4:1, 3:1, 2:1, 3:2, 1:1 and 0:1), and stirred at 80°C until completely transparent and uniform. Choosing the appropriate PVDF molecular weight and solvent ratio can optimize the mechanical and optical properties of the film.

[0047] 1.2 Dissolution of perovskite components

[0048] Set the molar ratio of perovskite precursors, such as lead halide perovskite materials such as CsPbX3 (X = Cl, Br, I), CH3NH3PbX3 (X = Cl, Br, I), and other types of perovskite materials such as methylamine lead iodide (MAPbI3) and formamidine lead iodide (FAPbI3). The specific steps are as follows:

[0049] Dissolve 0.5 mmol PbBr2 and 0.5 mmol CsBr (or other perovskite precursors) in 10 mL DMF and stir for 30 minutes to ensure complete dissolution to form a uniform perovskite precursor solution. According to the required color and performance requirements, adjust the molar ratio of the perovskite precursor, for example, CsI content of 0.03 mmol, and DMAPbI3 / DMAPbBr3 mixtures of different molar ratios (3:1, 2:1, 1:1, 1:2 and 1:3, respectively) are dissolved in the above-prepared PVDF solution to ensure that the perovskite component is evenly dispersed in the polymer matrix.

[0050] 2. Synthesis of Perovskite Quantum Dots / PVDF Composite Film

[0051] The precursor solution prepared above is evenly coated on the surface of the glass substrate to form a transparent film with uniform thickness. The specific steps are as follows:

[0052] The precursor solution is uniformly coated on the glass substrate by spin coating, spray coating or blade coating to form a thin film with a thickness of about 2 μm.

[0053] The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF / DMSO solvent and in-situ growing perovskite quantum dots to finally obtain a perovskite quantum dot / PVDF composite film.

[0054] The film may also contain other additives before treatment, such as plasticizers, cross-linking agents, antioxidants, etc., to further improve its mechanical properties and chemical stability.

[0055] Example 1

[0056] (1) Preparation step: Preparation of perovskite quantum dots / PVDF composite membrane.

[0057] 0.5 mmol PbBr2 and 0.5 mmol CsBr were dissolved in 10 mL DMF and stirred for 30 minutes to form a uniform perovskite precursor solution. Subsequently, the precursor solution was mixed with 10 wt% PVDF solution (molecular weight 800,000 Da) in a volume ratio of 1:9 and ultrasonically dispersed for 30 minutes to ensure that the perovskite precursor was evenly distributed in the PVDF matrix. The mixed solution was evenly coated on a glass substrate by spin coating to form a film with a thickness of about 8 μm. The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF solvent and in situ growing CsPbBr3 perovskite quantum dots, and finally a green luminescent perovskite quantum dot / PVDF composite film was obtained.

[0058] (2) Immersion treatment: The composite membrane was immersed in 1 M NaOH solution for 1 hour at a temperature of 25 °C and carried out under ultrasonic conditions to ensure the uniformity of the treatment.

[0059] (3) Cleaning and drying: The composite membrane after immersion treatment was cleaned with deionized water for 3 times, 5 minutes each time, and then dried at 60°C for 2 hours.

[0060] Comparative Example 1

[0061] (1) Preparation step: Preparation of perovskite quantum dots / PVDF composite membrane.

[0062] 0.5 mmol PbBr2 and 0.5 mmol CsBr were dissolved in 10 mL DMF and stirred for 30 minutes to form a uniform perovskite precursor solution. Subsequently, the precursor solution was mixed with 10 wt% PVDF solution (molecular weight 800,000 Da) in a volume ratio of 1:9 and ultrasonically dispersed for 30 minutes to ensure that the perovskite precursor was evenly distributed in the PVDF matrix. The mixed solution was evenly coated on a glass substrate by spin coating to form a film with a thickness of about 8 μm. The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF solvent and in situ growing CsPbBr3 perovskite quantum dots, and finally a green luminescent perovskite quantum dot / PVDF composite film was obtained.

[0063] (2) Cleaning and drying: Clean with deionized water three times, 5 minutes each time, and then dry at 60°C for 2 hours.

[0064] See also Figure 1 , Figure 1 The luminescence spectra of Example 1 and Comparative Example 1 are compared. The test results show that the luminescence position of the treated film remains almost unchanged, and the luminescence intensity at 514 nm is increased by 42.6%. The double 85 aging test shows that the aging time of the film is increased from the original 12 hours to 48 hours, showing a significant improvement in stability.

[0065] Example 2

[0066] (1) Preparation step: Preparation of perovskite quantum dots / PVDF composite membrane.

[0067] 0.2 mmol PbBr2 and 0.2 mmol CH3NH3Br were dissolved in 10 mL DMF and stirred for 30 minutes to form a uniform perovskite precursor solution. Subsequently, the precursor solution was mixed with 15 wt% PVDF solution (molecular weight 600,000 Da) in a volume ratio of 1:8 and ultrasonically dispersed for 1 hour to ensure that the quantum dots were uniformly dispersed in the PVDF matrix. The mixed solution was uniformly coated on a flexible plastic substrate by a doctor blade method to form a film with a thickness of about 7 μm. The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF solvent and in situ growing CH3NH3PbBr3 perovskite quantum dots, and finally a green luminescent perovskite quantum dot / PVDF composite film was obtained.

[0068] (2) Immersion treatment: The perovskite quantum dot / PVDF composite membrane was treated in 5 M NaOH solution for 30 min at a treatment temperature of 50 °C.

[0069] (3) Cleaning and drying: The treated composite membrane was cleaned with deionized water for 3 times, 5 minutes each time, and then dried at 80 °C for 4 hours.

[0070] (4) Annealing: The cleaned and dried composite membrane was annealed at 60°C for 1 hour.

[0071] Comparative Example 2

[0072] Compared with Example 2, Comparative Example 2 was not subjected to immersion treatment.

[0073] See also Figure 2 , Figure 2 The luminescence spectra of the luminescent films obtained in Example 2 and Comparative Example 2 are compared. Performance tests show that the luminescence intensity of the treated film at 515 nm is increased by 71.6% ( Figure 2 ). The double 85 aging test shows that the aging time of the film is increased from the original 2 hours to 12 hours, showing excellent stability and luminous efficiency.

[0074] Example 3

[0075] (1) Preparation step: Preparation of perovskite quantum dots / PVDF composite membrane.

[0076] 0.8 mmol DMAPbBr3 and 0.8 mmol CsBr were dissolved in 5 mL DMF and 3 mL DMSO and stirred for 30 minutes to form a uniform perovskite precursor solution. Subsequently, the precursor solution was mixed with 10 wt% PVDF solution (molecular weight 800,000 Da) in a volume ratio of 1:9 and ultrasonically dispersed for 30 minutes to ensure that the perovskite precursor was evenly distributed in the PVDF matrix. The mixed solution was evenly coated on a glass substrate by spin coating to form a film with a thickness of about 8 μm. The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF and DMSO solvents and in situ growing CsPbBr3 perovskite quantum dots, and finally a green luminescent perovskite quantum dot / PVDF composite film was obtained.

[0077] (2) Immersion treatment: The composite membrane was treated in 1 M KOH solution for 2 h at a temperature of 25 °C.

[0078] (3) Cleaning and drying: The composite film obtained by the immersion treatment was cleaned with deionized water for 3 times, each time for 5 minutes, and then dried at 40°C for 6 hours to obtain the perovskite quantum dot / PVDF luminescent film.

[0079] Comparative Example 3

[0080] Compared with Example 3, Comparative Example 3 was not subjected to immersion treatment.

[0081] Figure 3 The luminescence spectra of the luminescent films obtained in Example 3 and Comparative Example 3 are compared. The test results show that the luminescence intensity of the treated film at 516 is increased by 68.4% ( Figure 3 ). The double 85 aging test showed that the aging time of the film was increased from the original 13 hours to 48 hours, showing good long-term stability.

[0082] Example 4

[0083] (1) Preparation step: Preparation of perovskite quantum dots / PVDF composite membrane.

[0084] 0.35 mmol PbBr2 and 0.35 mmol CsBr were dissolved in 10 mL DMF and stirred for 30 minutes to form a uniform perovskite precursor solution. Subsequently, the precursor solution was mixed with 8 wt% PVDF solution (molecular weight 650,000 Da) in a volume ratio of 1:9 and ultrasonically dispersed for 1 hour to ensure that the perovskite quantum dots were evenly distributed in the PVDF matrix. The mixed solution was evenly coated on a PET substrate by spraying to form a film with a thickness of about 2.5 μm. The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF solvent and in situ growing CsPbI3 perovskite quantum dots, and finally a red-luminescent perovskite quantum dot / PVDF composite film was obtained.

[0085] (2) Immersion treatment: The composite membrane was treated in 10 M Na2CO3 solution for 1 hour at a temperature of 25°C.

[0086] (3) Cleaning and drying: The composite membrane after immersion treatment was cleaned with deionized water for 3 times, each time for 5 minutes; the cleaned and dried composite membrane was dried at 60°C for 3 hours.

[0087] (4) Annealing treatment: The cleaned and dried composite membrane is annealed at 80°C for 1 hour.

[0088] Comparative Example 4

[0089] Compared with Example 4, Comparative Example 4 was not subjected to immersion treatment.

[0090] Figure 4 The luminescence spectra of the luminescent films obtained in Example 4 and Comparative Example 4 are compared. Performance tests show that the luminescence intensity of the treated film at 512 nm is increased by 80% ( Figure 4 ). The double 85 aging test shows that the aging time of the film is increased from the original 6 hours to 29 hours, showing excellent stability and luminous efficiency, and is suitable for flexible display devices.

[0091] Example 5

[0092] (1) Preparation step: Preparation of perovskite quantum dots / PVDF composite membrane.

[0093] 0.5 mmol PbI2, 0.5 mmol PbBr2 and 0.5 mmol CsBr were dissolved in 10 mL DMF and stirred for 30 minutes to form a uniform perovskite precursor solution. Subsequently, the precursor solution was mixed with 10 wt% PVDF solution (molecular weight 800,000 Da) in a volume ratio of 1:9 and ultrasonically dispersed for 30 minutes to ensure that the perovskite quantum dots were evenly distributed in the PVDF matrix. The mixed solution was evenly coated on a silicon substrate by spin coating to form a film with a thickness of about 2 μm. The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF solvent and in situ growing CsPb(Br / I)3 perovskite quantum dots, and finally a red-light-emitting perovskite quantum dot / PVDF composite film was obtained.

[0094] (2) Immersion treatment: The composite membrane was treated in 2 M NaOH solution for 10 h.

[0095] (3) Cleaning and drying: The composite membrane after immersion treatment was cleaned with deionized water for 3 times, 5 minutes each time, and then dried at 60°C for 4 hours.

[0096] (4) Annealing treatment: The cleaned and dried composite membrane was annealed at 110°C for 40 minutes.

[0097] Comparative Example 5

[0098] Compared with Example 5, Comparative Example 5 was not subjected to immersion treatment.

[0099] Figure 5 The luminescence spectra of the luminescent films obtained in Example 5 and Comparative Example 5 are compared. The test results show that the luminescence intensity of the treated film at 625 nm is increased by 131% ( Figure 5 ). The double 85 aging test shows that the aging time of the film is increased from the original 4 hours to 18 hours, showing excellent long-term stability and is suitable for high-performance optoelectronic devices.

[0100] Example 6

[0101] (1) Preparation step: preparing a perovskite quantum dot / PVDF composite membrane. (Same as Example 5)

[0102] 0.5 mmol PbI2, 0.5 mmol PbBr2 and 0.5 mmol CsBr were dissolved in 10 mL DMF and stirred for 30 minutes to form a uniform perovskite precursor solution. Subsequently, the precursor solution was mixed with 10 wt% PVDF solution (molecular weight 800,000 Da) in a volume ratio of 1:9 and ultrasonically dispersed for 30 minutes to ensure that the perovskite quantum dots were evenly distributed in the PVDF matrix. The mixed solution was evenly coated on a silicon substrate by spin coating to form a film with a thickness of about 2 μm. The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF solvent and in situ growing CsPb(Br / I)3 perovskite quantum dots, and finally a red-light-emitting perovskite quantum dot / PVDF composite film was obtained.

[0103] (2) Immersion treatment: The composite membrane was treated in 20 M NaOH solution at 100 °C for 1 min.

[0104] (3) Cleaning and drying: The composite membrane after immersion treatment was cleaned with deionized water for 3 times, 5 minutes each time, and then dried at 80°C for 2 hours.

[0105] (4) Annealing treatment: The cleaned and dried composite membrane is annealed at 150°C for 10 minutes.

[0106] Example 7

[0107] (1) Preparation step: preparing a perovskite quantum dot / PVDF composite membrane. (Same as Example 5)

[0108] 0.5 mmol PbI2, 0.5 mmol PbBr2 and 0.5 mmol CsBr were dissolved in 10 mL DMF and stirred for 30 minutes to form a uniform perovskite precursor solution. Subsequently, the precursor solution was mixed with 10 wt% PVDF solution (molecular weight 800,000 Da) in a volume ratio of 1:9 and ultrasonically dispersed for 30 minutes to ensure that the perovskite quantum dots were evenly distributed in the PVDF matrix. The mixed solution was evenly coated on a silicon substrate by spin coating to form a film with a thickness of about 2 μm. The substrate coated with the precursor solution was placed in a blast furnace and treated for 15 minutes in an air environment at 65°C by evaporating the DMF solvent and in situ growing CsPb(Br / I)3 perovskite quantum dots, and finally a red-light-emitting perovskite quantum dot / PVDF composite film was obtained.

[0109] (2) Immersion treatment: The composite membrane was treated in 0.1 M NaOH solution at 60 °C for 10 h.

[0110] (3) Cleaning and drying: The composite membrane after immersion treatment was cleaned with deionized water for 3 times, 5 minutes each time, and then dried at 60°C for 6 hours.

[0111] (4) Annealing treatment: The cleaned and dried composite membrane is annealed at 20°C for 2 hours.

[0112] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0113] The parts not elaborated in detail in the description of the present invention belong to the known technology in the art. The above embodiments are provided only for the purpose of describing the present invention, and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. Various equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be included in the scope of the present invention.

Claims

1. A method for preparing a perovskite quantum dot / PVDF luminescent film, characterized in that: The preparation method comprises soaking the perovskite quantum dot / PVDF composite membrane, wherein the soaking treatment comprises soaking the perovskite quantum dot / PVDF composite membrane in a solution with a pH value greater than 7.

2. The method for preparing the perovskite quantum dot / PVDF luminescent film according to claim 1, characterized in that: The OH of the solution - The molar concentration ranges from 0.1 M to 20 M.

3. The method for preparing the perovskite quantum dot / PVDF luminescent film according to claim 1, characterized in that: The soaking treatment may be performed for a period of 1 minute to 10 hours.

4. The method for preparing the perovskite quantum dot / PVDF luminescent film according to claim 3, characterized in that: The soaking treatment may last for 30 minutes to 5 hours.

5. The method for preparing the perovskite quantum dot / PVDF luminescent film according to claim 1, characterized in that: The soaking treatment temperature is 20° C. to 100° C.; or, the soaking treatment is performed under stirring or ultrasonic conditions.

6. The method for preparing the perovskite quantum dot / PVDF luminescent film according to claim 1, characterized in that: The preparation method further comprises the steps of cleaning and drying the composite membrane after the immersion treatment.

7. The method for preparing the perovskite quantum dot / PVDF luminescent film according to claim 6, characterized in that: After cleaning and drying, the preparation method further comprises the step of annealing the composite membrane, the annealing temperature is 20° C. to 150° C., and the annealing time is 10 minutes to 2 hours.

8. The method for preparing the perovskite quantum dot / PVDF luminescent film according to any one of claims 1 to 7, characterized in that: The solution is a hydroxide solution, a carbonate solution or a bicarbonate solution.

9. The perovskite quantum dot / PVDF luminescent film prepared according to any one of claims 1 to 8.

10. The use of the perovskite quantum dot / PVDF luminescent film according to claim 9, characterized in that: The perovskite quantum dot / PVDF luminescent film is applied to Micro-LED, quantum dot light-emitting diode display, solar cell or photodetector.

Citation Information

Patent Citations

  • Quantum dot light emitting layer and quantum dot light emitting diode

    CN111244308A

  • Perovskite quantum dot film green light regulation and control and preparation method and application thereof

    CN114621759A

  • Method for improving performance and stability of perovskite solar cell

    CN114665025A

  • Perovskite quantum dot film, preparation method thereof and light-emitting diode

    CN115224226A

  • Perovskite quantum dot film, preparation method thereof and light-emitting diode

    CN116600619A

Cited By

  • FAPbI3-PVDF composite film as well as preparation method and application thereof

    CN121293966A